Pressure-sensitive aluminum paste and preparation method thereof
By using pressure-sensitive aluminum slurry prepared from aluminum powder, aluminum-zinc alloy powder, nickel powder, glass powder and specific nanomaterials in zinc oxide varistor, the problems of high cost of precious metal powder and complicated sintering process are solved, and the problem of high cost and complicated sintering process is solved. Preparation of low-cost, high-performance base metal conductive pastes.
Patent Information
- Application Number
- CN202411450254.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, when preparing zinc oxide varistors, precious metal powders are expensive, resulting in high costs. The sintering process has problems such as high temperature and environmental pollution, making it difficult to achieve low-cost and high-performance base metal conductive paste.
Aluminum powder, aluminum-zinc alloy powder, nickel powder, glass powder and specific additives (such as nickel nanowires, aluminum nanowires and graphene) are used to prepare pressure-sensitive aluminum slurry in specific proportions. It is prepared by grinding and mixing to control the amount of nickel powder added and Additive composition to optimize slurry performance.
It realizes the characteristics of low cost, strong adhesion and high sintering efficiency of pressure-sensitive aluminum slurry, reduces the firing temperature, improves the stackability and adhesion of the slurry, and promotes market-oriented production.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pressure-sensitive aluminum paste, and more specifically, relates to a pressure-sensitive aluminum paste and a preparation method thereof. Background Art
[0002] With the extensive application of electronic computers, integrated circuits, and solar cells, people are paying more and more attention to the development and research of electronic pastes. Electronic pastes are mainly used in resistors, capacitors, inductors, surface mounting technology, new energy materials, and many other aspects. Electronic pastes are an indispensable basic raw material in the manufacturing process of electronic information materials and their components, and play a vital role in the electronic information industry and market economy.
[0003] The conductive fillers in electronic pastes are not only made of precious metal powders such as gold, silver, and platinum, but also base metal powders such as copper, aluminum, and nickel. As the price of precious metal powders gradually rises, the situation in which zinc oxide varistor electrode materials are mainly made of precious metals has gradually withdrawn from the fierce market competition, and the base metalization of zinc oxide varistor electrodes has become the most important goal at present. The technology of preparing electrodes with base metal conductive pastes at low cost and high performance has become a hot topic in the industry.
[0004] Aluminum paste is used to replace silver paste and copper paste to prepare zinc oxide varistors. The sintering peak temperature can be reduced by optimizing the aluminum paste sintering process and adjusting the formula. This has significant technical and economic significance for shortening the production process, reducing environmental pollution, saving costs, and promoting the market-oriented production of varistor thick films.
[0005] Conductive aluminum paste is composed of aluminum powder, organic carrier, glass powder and additives. The aluminum powder particle size used in conductive aluminum paste for different purposes is different. Most of them use spherical aluminum powder with a particle size of less than 10μm. Glass powder is a binder mixed with various oxides. Commonly used glass powder materials include Bi2O3, B2O3, ZnO, SiO2, Al2O3, etc. Some other oxides (K2O, MgO, etc.) are also added to the glass to adjust the properties of the glass itself (low glass transition temperature, wettability, chemical stability, thermal stability, corrosion resistance, etc.), so that the glass and the substrate have a matching thermal expansion coefficient, which can better combine with the substrate to provide good adhesion. The organic carrier is composed of additives, organic solvents, and thickeners, which provide better printing performance by adjusting the viscosity of the paste. A small amount of additives is added to the paste to eliminate the air pockets generated during the sintering process and reduce the warping problems generated during the sintering process.
[0006] The invention provides a pressure-sensitive aluminum paste, which has the characteristics of low cost, excellent adhesion, high sintering efficiency and the like. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a pressure-sensitive aluminum paste and a preparation method thereof. By weight: it includes the following components: 60 to 85 parts of aluminum powder and aluminum-zinc alloy powder, wherein zinc accounts for 10 to 20 parts of the aluminum powder and the aluminum-zinc alloy powder, and the mass fraction of aluminum in the aluminum-zinc alloy powder is 60 to 80%; 2 to 9 parts of nickel powder; the particle size of the nickel powder is 0.4 to 0.8 μm; 4 to 8 parts of organic carrier; 2 to 4 parts of glass powder; 1 to 3 parts of additives. By controlling the amount of nickel powder added and the additives of specific composition, the pressure-sensitive aluminum paste prepared by the present invention has the characteristics of low cost, strong adhesion, high sintering efficiency, etc.
[0008] The purpose of the present invention is to provide a pressure-sensitive aluminum paste.
[0009] Another object of the present invention is to provide a method for preparing a pressure-sensitive aluminum paste.
[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0011] A pressure-sensitive aluminum paste, comprising the following components by weight:
[0012] 60 to 85 parts of aluminum powder and aluminum-zinc alloy powder, wherein zinc accounts for 10 to 20 parts of the aluminum powder and the aluminum-zinc alloy powder, and the mass fraction of aluminum in the aluminum-zinc alloy powder is 60 to 80%;
[0013] 2 to 9 parts of nickel powder; the particle size of the nickel powder is 0.4 to 0.8 μm;
[0014] Organic carrier: 4-8 parts;
[0015] 2-4 parts of glass powder;
[0016] 1 to 3 parts of additives.
[0017] Preferably, the particle size of the aluminum-zinc alloy powder is 1 to 3 μm; and the particle size of the aluminum powder is 0.5 to 1.5 μm.
[0018] In a preferred embodiment, the composition of the glass powder is B2O3-ZnO-AL2O3, wherein the B2O3 accounts for 30-40wt%, the ZnO accounts for 50-60wt% and the balance is Al2O3.
[0019] In a further preferred embodiment, the additives are nickel nanowires, aluminum nanowires and graphene; the mass ratio of the nickel nanowires, aluminum nanowires and graphene is 2-4:1:0.4-0.8.
[0020] Preferably, the nickel nanowire has a length of 50-250 nm and an aspect ratio of 5-25.
[0021] Preferably, the length of the aluminum nanowires includes 10-30 nm, 100-200 nm and 500-1000 nm; the aspect ratio of the aluminum nanowires of 10-30 nm is 2-6; the aspect ratio of the aluminum nanowires of 100-200 nm is 10-20; the aspect ratio of the aluminum nanowires of 500-1000 nm is 25-50; the mass ratio of the aluminum nanowires of 10-30 nm, the aluminum nanowires of 100-200 nm and the aluminum nanowires of 500-1000 nm is 1:2-4:0.6-1.
[0022] In a further preferred embodiment, the organic carrier is composed of terpineol and ethyl cellulose, and the mass ratio of terpineol to ethyl cellulose is 7-9:1-3.
[0023] Based on the above-mentioned method for preparing a pressure-sensitive aluminum paste, the preparation method comprises the following steps:
[0024] Aluminum powder, aluminum-zinc alloy powder, nickel powder and glass powder are ground and mixed for 10 to 30 minutes, and then an organic carrier and additives are added, and the grinding and mixing are continued for 20 to 40 minutes to obtain a pressure-sensitive aluminum paste.
[0025] The present invention has the following beneficial effects:
[0026] The present invention can effectively reduce the firing temperature by adding aluminum-zinc alloy powder and glass powder, and can improve the stacking property of the slurry by adding nickel. By adopting additives composed of nickel nanowires, aluminum nanowires and graphene, the adhesion and sintering performance can be effectively improved, and the firing rate is also improved. The pressure-sensitive aluminum paste of the present invention has low cost and excellent performance. DETAILED DESCRIPTION
[0027] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0028] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0029] Example 1
[0030] A pressure-sensitive aluminum paste, comprising the following components by weight:
[0031] 75 parts of aluminum powder and aluminum-zinc alloy powder; wherein, in the aluminum powder and the aluminum-zinc alloy powder, zinc accounts for 15 parts; in the aluminum-zinc alloy powder, the mass fraction of aluminum is 70%; the particle size of the aluminum-zinc alloy powder is 2 μm; the particle size of the aluminum powder is 1 μm;
[0032] 6 parts of nickel powder; the particle size of the nickel powder is 0.6 μm;
[0033] Organic carrier: 6 parts;
[0034] 3 parts of glass powder; the composition of the glass powder is B2O3-ZnO-AL2O3, in which B2O3 accounts for 35wt% and ZnO accounts for 55wt%; the balance is Al2O3;
[0035] 2 parts of additives;
[0036] The additives are nickel nanowires, aluminum nanowires and graphene; the mass ratio of the nickel nanowires, aluminum nanowires and graphene is 3:1:0.6: the length of the nickel nanowires is 150nm, and the aspect ratio is 15; the lengths of the aluminum nanowires include 20nm, 150nm and 750nm, and the aspect ratio of the 20nm aluminum nanowire is 4; the aspect ratio of the 150nm aluminum nanowire is 15; the aspect ratio of the 800nm aluminum nanowire is 40; the mass ratio of the 20nm aluminum nanowires, the 150nm aluminum nanowires and the 800nm aluminum nanowires is 1:3:0.8.
[0037] The organic carrier is composed of terpineol and ethyl cellulose, and the mass ratio between the two is 8:2.
[0038] A method for preparing a pressure-sensitive aluminum paste comprises the following steps:
[0039] Aluminum powder, aluminum-zinc alloy powder, nickel powder and glass powder were ground and mixed for 20 minutes, and then an organic carrier and additives were added, and the grinding and mixing were continued for 30 minutes to obtain a pressure-sensitive aluminum paste.
[0040] Example 2
[0041] A pressure-sensitive aluminum paste, comprising the following components by weight:
[0042] 85 parts of aluminum powder and aluminum-zinc alloy powder; wherein, in the aluminum powder and the aluminum-zinc alloy powder, zinc accounts for 20 parts; in the aluminum-zinc alloy powder, the mass fraction of aluminum is 60%; the particle size of the aluminum-zinc alloy powder is 3 μm; the particle size of the aluminum powder is 0.5 μm;
[0043] 2 parts of nickel powder; the particle size of the nickel powder is 0.4 μm;
[0044] Organic carrier: 8 parts;
[0045] 2 parts of glass powder; the composition of the glass powder is B2O3-ZnO-AL2O3, in which B2O3 accounts for 40wt% and ZnO accounts for 50wt%; the balance is Al2O3;
[0046] 3 parts of additives;
[0047] The additives are nickel nanowires, aluminum nanowires and graphene; the mass ratio of the nickel nanowires, aluminum nanowires and graphene is 4:1:0.4: the length of the nickel nanowire is 250nm, and the aspect ratio is 25; the length of the aluminum nanowire includes 10nm, 200nm and 500nm, and the aspect ratio of the 10nm aluminum nanowire is 2; the aspect ratio of the 200nm aluminum nanowire is 20; the aspect ratio of the 500nm aluminum nanowire is 25; the mass ratio of the 10nm aluminum nanowire, the 200nm aluminum nanowire and the 500nm aluminum nanowire is 1:4:0.6;
[0048] The organic carrier is composed of terpineol and ethyl cellulose, and the mass ratio between the two is 9:1.
[0049] A method for preparing a pressure-sensitive aluminum paste is the same as that in Example 1.
[0050] Example 3
[0051] A pressure-sensitive aluminum paste, comprising the following components by weight:
[0052] 60 parts of aluminum powder and aluminum-zinc alloy powder; wherein, in the aluminum powder and the aluminum-zinc alloy powder, zinc accounts for 10 parts; in the aluminum-zinc alloy powder, the mass fraction of aluminum is 80%; the particle size of the aluminum-zinc alloy powder is 1 μm; the particle size of the aluminum powder is 1.5 μm;
[0053] 9 parts of nickel powder; the particle size of the nickel powder is 0.8 μm;
[0054] Organic carrier: 4 parts;
[0055] 4 parts of glass powder; the composition of the glass powder is B2O3-ZnO-AL2O3, in which B2O3 accounts for 30wt% and ZnO accounts for 60wt%; the balance is Al2O3;
[0056] 1 part of additive;
[0057] The additives are nickel nanowires, aluminum nanowires and graphene; the mass ratio of the nickel nanowires, aluminum nanowires and graphene is: 2:1:0.8: the length of the nickel nanowire is 50nm, and the aspect ratio is 5; the length of the aluminum nanowire includes 30nm, 100nm and 1000nm, and the aspect ratio of the 30nm aluminum nanowire is: 6; the aspect ratio of the 100nm aluminum nanowire is 10; the aspect ratio of the 1000nm aluminum nanowire is 50; the mass ratio of the 30nm aluminum nanowire, the 100nm aluminum nanowire and the 1000nm aluminum nanowire is 1:2:1;
[0058] The organic carrier is composed of terpineol and ethyl cellulose, and the mass ratio between the two is 7:3.
[0059] A method for preparing a pressure-sensitive aluminum paste is the same as that in Example 1.
[0060] Comparative Example 1
[0061] Comparative Example 1 is substantially the same as Example 1, except that the nickel powder is 10 parts.
[0062] Comparative Example 2
[0063] Comparative Example 2 is substantially the same as Example 1, except that the nickel powder is 1 part.
[0064] Comparative Example 3
[0065] Comparative Example 3 is basically the same as Example 1, except that: the lengths of the aluminum nanowires include 20 nm and 750 nm, the aspect ratio of the 20 nm aluminum nanowire is 4; the aspect ratio of the 800 nm aluminum nanowire is 40; the mass ratio of the 20 nm aluminum nanowire and the 800 nm aluminum nanowire is 4:0.8.
[0066] Comparative Example 4
[0067] Comparative Example 4 is basically the same as Example 1, except that: the lengths of the aluminum nanowires include 20 nm and 750 nm, the aspect ratio of the 20 nm aluminum nanowire is 4; the aspect ratio of the 800 nm aluminum nanowire is 40; the mass ratio of the 20 nm aluminum nanowire to the 800 nm aluminum nanowire is 1:3.8.
[0068] Comparative Example 5
[0069] Comparative Example 5 is substantially the same as Example 1, except that the additives are nickel nanowires and graphene; and the mass ratio of the nickel nanowires to the graphene is 4:0.6.
[0070] Comparative Example 6
[0071] Comparative Example 6 is substantially the same as Example 1, except that the additives are nickel nanowires and graphene; and the mass ratio of the nickel nanowires to the graphene is 3:1.6.
[0072] The performance of Examples 1-3 and Comparative Examples 1-6 was measured by the following method:
[0073] 3 g of the prepared aluminum paste was manually screen-printed on a substrate (the substrate was a circular ZnO substrate with a diameter of Φ12 mm) using a 250-mesh screen, leveled for 15 minutes, dried at 150°C for 10 minutes, and the dried sample was placed in a high-temperature tube furnace and sintered at 550°C for 10 minutes.
[0074] The resistance was measured by a digital ohmmeter (SD200), and the adhesion was measured by a spiral tensile machine (SLJ).
[0075] The specific test results are shown in Table 1:
[0076] Square resistance (Ω / □) <![CDATA[Adhesion force (N / mm 2 )]]> Example 1 0.23 16.3 Example 2 0.28 15.8 Example 3 0.25 16.1 Comparative Example 1 0.39 14.3 Comparative Example 2 0.36 14.6 Comparative Example 3 0.33 15.2 Comparative Example 4 0.31 15.4 Comparative Example 5 0.46 12.3 Comparative Example 6 0.43 12.8
[0077] It can be seen from Table 1 that the varistor aluminum paste prepared by the present invention has excellent adhesion and excellent electrical properties. Moreover, by comparing the embodiments with the comparative examples, it can be seen that the present invention has a suitable amount of nickel powder added, as well as additives with a specific composition and ratio, so that the varistor aluminum paste prepared by the present invention has the characteristics of low cost, strong adhesion and excellent electrical properties.
[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A pressure-sensitive aluminum paste, characterized in that: By weight: Includes the following components: 60 to 85 parts of aluminum powder and aluminum-zinc alloy powder, wherein zinc accounts for 10 to 20 parts of the aluminum powder and the aluminum-zinc alloy powder, and the mass fraction of aluminum in the aluminum-zinc alloy powder is 60 to 80%; 2 to 9 parts of nickel powder; the particle size of the nickel powder is 0.4 to 0.8 μm; Organic carrier: 4-8 parts; 2-4 parts of glass powder; 1 to 3 parts of additives.
2. The pressure-sensitive aluminum paste according to claim 1, characterized in that: The particle size of the aluminum-zinc alloy powder is 1 to 3 μm; the particle size of the aluminum powder is 0.5 to 1.5 μm.
3. The pressure-sensitive aluminum paste according to claim 1, characterized in that: The composition of the glass powder is B2O3-ZnO-AL2O3.
4. The pressure-sensitive aluminum paste according to claim 3, characterized in that: The B2O3 accounts for 30-40wt%; the ZnO accounts for 50-60wt%; and the balance is Al2O3.
5. The pressure-sensitive aluminum paste according to claim 1, characterized in that: The additives are nickel nanowires, aluminum nanowires and graphene; the mass ratio of the nickel nanowires, aluminum nanowires and graphene is 2-4:1:0.4-0.
8.
6. The pressure-sensitive aluminum paste according to claim 5, characterized in that: The nickel nanowire has a length of 50-250 nm and an aspect ratio of 5-25.
7. The pressure-sensitive aluminum paste according to claim 5, characterized in that: The lengths of the aluminum nanowires include 10 to 30 nm, 100 to 200 nm and 500 to 1000 nm; the aspect ratio of the aluminum nanowires of 10 to 30 nm is 2 to 6; the aspect ratio of the aluminum nanowires of 100 to 200 nm is 10 to 20; the aspect ratio of the aluminum nanowires of 500 to 1000 nm is 25 to 50; the mass ratio of the aluminum nanowires of 10 to 30 nm, the aluminum nanowires of 100 to 200 nm and the aluminum nanowires of 500 to 1000 nm is 1:2 to 4:0.6 to 1.
8. The pressure-sensitive aluminum paste according to claim 1, characterized in that: The organic carrier consists of terpineol and ethyl cellulose.
9. The pressure-sensitive aluminum paste according to claim 8, characterized in that: The mass ratio of the terpineol to the ethyl cellulose is 7-9:1-3.
10. A method for preparing a pressure-sensitive aluminum paste according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: Aluminum powder, aluminum-zinc alloy powder, nickel powder and glass powder are ground and mixed for 10 to 30 minutes, and then an organic carrier and additives are added, and the grinding and mixing are continued for 20 to 40 minutes to obtain a pressure-sensitive aluminum paste.